Application de l’approche a barrieres multiples pour reduire les risques microbiens dans le secteur post-recolte des legumes irrigues avec des eaux usees. In French. [Applying the multiple-barrier approach for microbial risk reduction in the post-harvest sector of wastewater irrigated vegetables]. - Ilic, S.; Drechsel, Pay; Amoah, Philip; LeJeune, J. T. (2011)
Post-harvest interventions are an important component of a multiple-barrier approach for health-risk reduction of wastewater-irrigated crops as recommended by the 2006 edition of the WHO Guidelines for safe wastewater irrigation. This approach draws on principles of other risk-management approaches, in particular the hazard analysis and critical control point (HACCP) concept. Post-harvest measures are of particular importance as they can address possible on-farm precontamination, and also contamination that may occur after the crops leave the farm. Key factors influencing microbial contamination along the farm to fork pathway are basic hygiene and temperature management. Both factors are, however, hardly under control in most developing countries where microbial contamination and proliferation are supported by low education, limited risk awareness, rudimentary technical infrastructure and unenforced regulations. In the face of these challenges, the most successful strategies to enhance food safety will involve interventions at multiple control points along the production chain, with emphasis on local safety targets and innovative educational programmes fitting local knowledge, culture and risk perceptions. The WHO (2006) recommended health-based targets for risk reduction in wastewater irrigation provide the required flexibility for risk mitigation in line with the concept of food-safety objectives (FSO).